Vidas Secas e aspectos da reificação - Rabello, Rosana Baú (2015)
From History and Class Consciousness (2012), of Georg Lukacs, we establish a reading on reification's aspects in "Vidas Secas" (2008), by Graciliano Ramos, who addresses the dehumanization and the reified consciousness and speaks of social condition of characters like refugees.